The level of attrition in domestic violence: A valid indicator of the efficiency of a criminal justice system?. (May 2020) - Chopin, Julien; Aebi, Marcelo F.
This article studies the process of attrition through a follow-up of all cases of domestic violence registered by the police forces of one Swiss canton in the first half of 2012 ( N = 592) as they pass to the prosecution and the court stage of criminal justice proceedings. The results show that the attrition rate found in Switzerland (80 percent) is lower than the rate usually found in the United Kingdom. This rate is explained by the fact that domestic violence is usually treated by academics as a homogeneous construct, but it is in fact composed of a large variety of offences and, in practice, the vast majority of those that are reported to the police would not entail a custodial sentence.